Andragogy in university education: The perception of undergraduate professors: the perception of undergraduate professors - Ferreira, Tássia Fernandes; Magalhães Junior, Antônio Germano; Nóbrega-Therrien, Silvia Maria (Universidade Estadual de Campinas, 2022)
Andragogy and its assumptions contain fundamental elements for the development of adult teaching and learning, covering specific issues that require attention from educators. In the meantime, this paper aims to understand the perception of undergraduate professors about the importance of Malcolm Knowles' andragogical assumptions. To do this, the following question was raised: “Even though undergraduate professors may not know what Andragogy is specifically, do they perceive its assumptions as important?” We used the mixed methods approach (JOHNSON; ONWUEGBUZIE, 2004), with the application of instruments with a quantitative bias and graphs, and with qualitative analysis. The subjects of this research were 21 professors of higher education in undergraduate courses, responding to an online questionnaire, divided into two sections: questions that addressed the profile of teachers and questions about Andragogy and the degree of importance attributed to the six andragogical assumptions. According to the analysis, it was found that the six assumptions were classified by most of the 21 professors as important / very important with a small portion (2 professors, corresponding to 9.5%) that used the “not important” classification. Thus, it is considered that the central questioning of the research, mentioned above, was answered affirmatively. In view of the obtained results, the importance of spreading knowledge about Andragogy and its assumptions is reaffirmed, since it provides professors with greater theoretical foundations and subsidies for their practices, enabling them to reframe their teaching practices.